Nanotechnology in the Treatment of Glioblastoma Multiforme: Enhancing Radiotherapy and Chemotherapy with Nanoparticles - Chrzanowska, Emilia Gabriela; Kuźniar, Jakub Paweł; Szlążek, Julia; Ząbek, Adam Jan; Zagalska, Michalina; Turek, Marta; Tamborski, Tomasz; Grzebinoga, Adam; Roguska, Barbara; Kuźniar, Michał (Journal of Education, Health and Sport, 2025)
Introduction: Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor, associated with poor prognosis despite standard treatment modalities including surgery, radiotherapy, and chemotherapy. The limited efficacy of these therapies is due, in part, to the difficulty of complete tumor resection, the blood-brain barrier (BBB) hindering drug penetration, and the tumor’s resistance mechanisms to chemotherapy and radiotherapy. Nanoparticles (NPs) offer promising solutions for targeted drug delivery, potentially improving therapeutic outcomes. This review summarizes recent advances in nanoparticle-based therapies for GBM. Methods: A literature review was conducted by analyzing 38 scientific articles using PubMed and Google Scholar databases. Studies published within the last five years focusing on the application of nanoparticles in GBM treatment were included. Various types of nanoparticles, their mechanisms of action, and the potential benefits and limitations of their clinical use were discussed. Results: The literature indicates that nanoparticles enhance drug permeability across the BBB, improve tumor penetration, and increase treatment efficacy. Their use in GBM therapy enables more precise drug delivery, reduces systemic toxicity, and minimizes damage to healthy tissues. Furthermore, nanoparticles play a significant role in combination therapies, potentially leading to a synergistic therapeutic effect. Conclusions: Nanoparticles represent a novel and promising strategy for the treatment of GBM, offering targeted drug delivery and improved therapeutic outcomes. However, further research is needed to optimize nanoparticle formulations and to evaluate their long-term safety and efficacy in clinical settings.